2004
DOI: 10.1159/000069547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose Polymer on the Intercellular Junctions of Cultured Human Peritoneal Mesothelial Cells

Abstract: Background: Glucose polymer is an active osmotic agent that is increasingly used as an alternative to glucose in peritoneal dialysis fluids. It was recently reported that the duration of peritoneal dialysis can be extended by using glucose polymer in patients with poor ultrafiltration. We previously demonstrated that high glucose levels damage the intercellular junctions of cultured human peritoneal mesothelial cells (HPMC), but little is known about the influence of glucose polymer. Therefore, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…It has been shown that a high concentration of glucose, used as osmotic agent, is cytotoxic to peritoneal cells [5]. In this respect, we [4] and others [6] have reported a major contribution of glucose to the induction of angiogenesis and fibrosis in experimental PD models.…”
Section: Introductionmentioning
confidence: 60%
“…It has been shown that a high concentration of glucose, used as osmotic agent, is cytotoxic to peritoneal cells [5]. In this respect, we [4] and others [6] have reported a major contribution of glucose to the induction of angiogenesis and fibrosis in experimental PD models.…”
Section: Introductionmentioning
confidence: 60%
“…It contains abundant anionic sites and intercellular junctions that enable it to act as a biologic barrier to the passage of plasma molecules (26,27). The introduction of PD over 20 yr ago has allowed us to manipulate the peritoneal membrane to act as a dialyzing organ in which ultrafiltration and diffusion occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice with overexpression of ␤-catenin display severe polycystic lesions in glomeruli, proximal and distal tubules, and collecting ducts (17). Decreased ␤-catenin is associated with excess TGF-␤1 synthesis and dysfunction of peritoneal mesothelial cells in the presence of high glucose (18). We recently found that TGF-␤1 was involved in reactive oxygen radical-mediated fibronectin accumulation of high glucose-stressed mesangial cells and early renal injuries in diabetic rats (19).…”
mentioning
confidence: 99%